THE IMPACT OF DIGITAL PLATFORMS AND INTERNET MARKETING TOOLS ON THE ADAPTATION OF MARKETING STRATEGIES OF ENTERPRISES IN CONDITIONS OF CHANGE AND CRISIS - Bilyk, I.I. (The actual problems of regional economy development, 2025)
The article examines current trends in the development of digital platforms and e-commerce, in particular their impact on companies' marketing strategies in a changing business environment. The purpose of the work is to conduct a comprehensive analysis of key aspects related to the use of digital platforms, social networks, and online marketing tools to enhance the efficiency of e-commerce. Additionally, the study seeks to explore how marketing strategies can be adapted to contemporary conditions, with a specific focus on crisis scenarios, such as the ongoing military conflict in Ukraine. The study uses systematic and comparative data analysis methods to deeply study the effectiveness of various digital marketing tools and their impact on the competitiveness of businesses. The results of the study confirm that the integration of the latest technologies, such as artificial intelligence, blockchain, Internet of Things (IoT), chatbots and marketing automation, is a key factor for success in modern e-commerce. The scientific novelty of the work lies in identifying optimal approaches to adapting marketing strategies to changes in consumer behavior, as well as identifying the importance of innovative technologies for increasing personalization and security in communications with customers. The study underscores the importance of swiftly adapting marketing strategies during crises, which helps businesses maintain customer loyalty and achieve market stability. The practical significance of the study lies in developing recommendations for small and medium-sized businesses on the effective use of digital platforms to increase sales, improve customer engagement, and maintain competitive advantages in changing market conditions. The study also provides practical tools for adapting marketing strategies in times of instability and global crises, which is especially relevant in today's globalized world. Prospects for further scientific developments lie in an in-depth study of the integration of the latest technologies into marketing strategies in times of crisis, as well as the study of the long-term effects of businesses adapting to changes in the digital environment, which will allow creating new business development models based on digital platforms.